Bone mineral density in elderly patients with osteoarthrosis - N V Mitrofanova; T A Raskina; N V Mitrofanova; T A Raskina (Современная ревматология, 2008)
Objective: to study bone mineral density (BMD) in elderly patients with different clinical forms of osteoarthrosis (OA). Patients and methods. A hundred and fifty-five patients above 65 years of age, diagnosed as having OA according to the criteria developed by R. Altman were examined. In all the patients, anthropometric indices, duration of the disease, and degree of functional impairment were assessed and joint X-ray study and densitometry were made. According to the clinical form of the disease, the patients were divided into 3 groups (with signs of gonarthrosis, oligoarthrosis of the knee and hip joints, and polyosteoarthrosis). Results. Both the clinical and anthropometric characteristics of patients facilitated the development of osteopenia. Involvement of a larger number of joints into a pathological process was followed by a significant BMD reduction in the predominant number of patients with OA. With the more progressive X-ray stage of the disease, a significantly higher BMD was observed in the distal forearm of patients from all groups. The patients aged 75 years or older who had gonarthrosis and polyosteoarthrosis showed a significant reduction in BMD as compared with those of less than 75 years of age. A greater reduction in the T test was shown to correspond to less body weight. The examinees' inactivity correlated with decreased BMD. In patients with polyosteoarthritis, early onset and longer menopause negatively affected BMD in the distal forearm. Conclusion. Reduced distal forearm BMD in elderly patients with OA is associated with patients' older age and a longer menopause, less body weight, early menopause, and no regular exercises. Progression of the X-ray stage of OA correlates with increased bone density.